The level of depression, anxiety, and sleep quality in pregnancy during coronavirus disease 2019 pandemic. Issue 8 (1st June 2021) - Çolak, Sabri; Gürlek, Beril; Önal, Özgür; Yılmaz, Bülent; Hocaoglu, Cicek
Abstract: Aim: We aimed to evaluate the mental health and sleep quality of pregnant women in different trimesters during coronavirus disease 2019 (COVID‐19) pandemic and investigate the effect of quarantine and new lifestyle changes that come into our lives with pandemic with on this subject. Methods: It was conducted on pregnant women ( n = 149) who attended routine pregnancy prenatal visit during their pregnancy weeks. The data were collected using sociodemographic and clinical data form, Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep quality, Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) to evaluate maternal depression and anxiety. Results: A significant correlation was observed between the week of gestation and depression, anxiety, and defective sleep scores ( p < 0.001). A moderate positive correlation was found between the week of gestation and depression ( r : 0.628). A high level of positive correlation was found between the week of gestation and defective sleep quality and anxiety scores ( r : 0.858, r : 0.754). A statistically significant increase in depression, anxiety, and defective sleep quality was found in the group staying in home quarantine ( p = 0.002). Conclusion: This study showed that the COVID‐19 pandemic can cause depression, anxiety, and serious sleep disorders in pregnant women. The depression and anxiety scores of pregnant women in home quarantine were also found to be higher than the group not in quarantine. As the week of gestation progresses, mental health symptoms worsen and sleep quality deteriorates.